2020
DOI: 10.1177/1043454220909805
|View full text |Cite
|
Sign up to set email alerts
|

An Integrative Review of Factors Associated With Symptom Burden at the End of Life in Children With Cancer

Abstract: Children with cancer experience multiple symptoms at end of life (EOL) that impair their health-related quality of life. Using the Preferred Reporting Items for Systematic reviews and Meta-Analyses guidelines, this integrative literature review comprehensively summarized symptom experiences of children with cancer at EOL. The Cumulative Index to Nursing and Allied Health Literature (CINAHL), PubMed, and Academic Premier were searched between January 2007 to September 2019 for articles published in English usin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 52 publications
(212 reference statements)
1
8
0
Order By: Relevance
“…Dying children endure a high burden of physical and psychological symptoms. Prevalent symptoms include pain, fatigue, poor appetite, dyspnea, irritability, sleep disturbances, anxiety, sadness, fear of being alone, and fear of dying 9 . When symptoms are not optimally managed, suffering for the child and family is exacerbated 10 .…”
Section: Introductionmentioning
confidence: 99%
“…Dying children endure a high burden of physical and psychological symptoms. Prevalent symptoms include pain, fatigue, poor appetite, dyspnea, irritability, sleep disturbances, anxiety, sadness, fear of being alone, and fear of dying 9 . When symptoms are not optimally managed, suffering for the child and family is exacerbated 10 .…”
Section: Introductionmentioning
confidence: 99%
“… 39 A more recent review found that children with cancer had several concurrent symptoms during the end-of-life period. 40 Therefore, health care providers should ensure that the best prognostic information is provided to children with cancer and their parents to suggest less painful approaches for improving the quality of end-of-life, such as PPC. Despite parents’ knowledge regarding the discouraging prognosis, they might not feel deprived of hope if their children receive appropriate PPC.…”
Section: Discussionmentioning
confidence: 99%
“…Children with advanced cancer experience high symptom distress (Eche et al, 2020;Torres et al, 2019). Mothers felt stressed and helpless when they could not help their children.…”
Section: Conditions Related To Child and Mothermentioning
confidence: 99%